Foraging behaviours of stingless bees Heterotrigona itama cockerell and Geniotrigona thoracica Smith as potential pollinators to star fruit Averrhoa carambola L. - Wan Mohd Adnan, Wan Nur Asiah (2021)
Star fruit, Averrhoa carambola is Malaysia’s most exported exotic fruit and is mostly marketed overseas. The demand for this fruit increases yearly and sometimes exceeds the supply capacity. The low production of this fruit due to the pests and diseases also decreased the cultivation land. To improve the productivity of this fruit to prevent insect pest visitation and other diseases, star fruit trees have been planted in netting structure and there is a need to find a potential pollinator to enhance the fruit production. Stingless bee could be one potential pollinator to be introduced in the netting structure. Unfortunately, there is still a lack in knowledge on the foraging behaviours of Heterotrigona itama and Geniotrigona thoracica in order to confirm their potential as efficient pollinators of start fruit flowers. To fill the knowledge gap, this study was conducted at the Integrated Farm, Universiti Putra Malaysia (UPM) to i) investigate the foraging activities of two selected stingless bee species, G. thoracica and H. itama in relation to seasonal and abiotic factors, ii) determine the pollen resources taken by G. thoracica and H. itama, and construct the pollen profile as a baseline data, iii) assess the efficacy and compare their visitation rate to the flowers of star fruit. The observation of bees that flew in and out from their nest was made hourly from 0800 to 1600 hours. Pollens from their corbiculae legs were collected, examined and counted under light microscope and SEM. The flower visitation rates of these bees were calculated based on visitation frequency on star fruit flowers. Results showed that the daily foraging activities and foraging pattern of these two bee species were significantly different at various times of the day. The two bees were observed to be more actively foraging in the morning during 0900 hours to 1100 hours after which they slowed down until the end of the day. Nectar collection for G. thoracica (67,363 individuals) and H. itama (53,518 individuals) were significantly higher compared to pollen collection which were 11,075 individuals (G. thoracica) and 6,803 individuals (H. itama). Bee activities also varied at different time and seasons (wet and dry) of the year and was demonstrated by significant fluctuations in the number of foraging bees among all months of observations. The highest foraging activities were recorded in January 2015 (wet season) for both species, i.e., 12,303 individuals (G. thoracica) and 12,979 individuals (H. itama). The lowest foraging activities were recorded in September 2014 for G. thoracica (7,517 individuals) and in August for H. itama (1,960 individuals). Variations in abiotic factors such as temperature, relative humidity and light intensity at the study area significantly affected the bees’ foraging activities. Composition of plant diversity at the study site influenced the foraging activities of the two bee species. Three most preferred plant families were Oxalidaceae (1,342 individual pollens or 18% of the total pollens collected), Arecacea (1,064 individual pollens or 15%) and Fabaceae (722 individual pollens or 10%). Star fruit being a tree is the most preferred vegetation category from which the main pollen and nectar resources were obtained by the bees followed by shrubs, grass, herbs and vegetables. Pollens of star fruit were highly attractive to these two bees due to the aromatic odor produced by this tree. Performances of flower visitation rate of these bees were slightly higher for G. thoracica compared to H. itama (IVR G. thoracica = 0.47 ± 0.02; IVR H. itama = 0.12 ± 0.02). The number of bees and their visitation (G. thoracica) to the star fruit panicles proportionately increased with the increase in the number of flowers on the panicles. The visitation rates of G. thoracica and H. itama remained low and quite similar to each other due to similar resources and foraging activities, and total dependence on one resource in the net cage. In conclusion, G. thoracica and H. itama were more actively foraging in the morning and during wet season. G. thoracica preferred to visit bigger panicles with more flowers and their visitations also increased when the size of the panicles increased. Geniotrigona thoracica could be a potential pollinator of the star fruit tree compared to H. itama based on its slight advantage of having higher frequency of visitation to the star fruit flowers.